Pauca verba on the association between protein intake and sarcopenia in older adults - Hélio José Coelho-Júnior; Alejandro Álvarez-Bustos; Leocadio Rodriguez-Mañas; Francesco Landi; Emanuele Marzetti (The Journal of Nutrition, Health and Aging)
Sarcopenia is a prevalent neuromuscular condition among older adults, marked by significant reductions in muscle mass and strength, which result in notable impairments in physical performance. Modifications in lifestyle habits have been frequently highlighted as essential approaches to mitigate the progression of sarcopenia, with a particular focus on protein consumption. Over the past few decades, a wealth of knowledge has emerged, driven by both observational and experimental studies exploring various factors related to protein intake, such as amount, timing, and sources. This review provides a pauca verba overview of these findings, presenting a concise yet informative summary of key insights.